PENGARUH LINGKUNGAN KELUARGA TERHADAP HASIL BELAJAR SISWA SMP NEGERI 3 SEPONTI KABUPATEN KAYONG UTARA - Ani Karini; Mashudi Mashudi; Aminuyati Aminuyati (Universitas Tanjungpura, 2019)
AbstractThis research was inteded to know the effect of family environment on learning outcomes of eight (VIII) grade student on IPS subject in SMP Negeri 3 Seponti Kabupaten Kayong Utara. The method used in this research was descriptive method with relationship studies form. The data collection technique used in this research was direct communication , indirect communication, and documentation. The tools used in this research was questionnaire, interview, and documenter. The population in this research was 41 students of eight (VIII) grade students of SMP Negeri 3 Seponti Kabupaten Kayong Utara. The research result showed that calculated significance 0.004<0.05. Therefore,Ha accepted and Ho rejected. That means the family environment affected the learning outcomes and it can be showed by simple linear equation Y=50.850+0.172X and calculated hypothesis t-test>t table or 3.057>2.023. The effect size of family environment on learning outcome from coefficient determination test was 0.193 or 19.3%, which means that 19.3 % of the learning outcomes are influenced by the family environment and the other 80.7% are it self such as students intellectual factors and factors originating from the school environment.Keywords: Family Environment, Learning Outcomes